Analisa Persepsi Interpersonal Karyawan PT Minu Garment Sukses Pada Penggunaan Kata Umpatan Korea - Dalima Dalima; Elis Yulianti (Syntax Corporation, 2023)
This study aims to analyze organizational communication in the application of interpersonal perceptions in Minu Garment companies Success in the use of Korean swear words by Korean leaders which has an impact on employee psychological disruption. Participants in the study were employees of PT. Minu Garment Success which includes Top Management and Middle Management statff. Top management staff are Korean company leaders and middle management staff are Indonesian employees. This research is a qualitativedescriptive research with interview method. Based on this study, it was found that the application of interpersonal perception to employees was able to overcome the psychological impact in the use of Korean swear words.